2023
DOI: 10.2118/215837-pa
|View full text |Cite
|
Sign up to set email alerts
|

Research on a Typical Casing Failure during Drilling of Cement Plugs in Ultradeep Wells

Abstract: Summary Among the casing failures in 46 ultradeep wells in a particular block, 11 ultradeep wells had the same casing failure forms occur during the drilling of cement plugs. The casing failure forms are local bending deformation and local internal pressure damage, which eventually led to a local burst failure of the casing in the 11 typical ultradeep wells. Therefore, a casing strength checking model is established to investigate the primary reasons for the local burst failure of the casing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Goodwin, K. and Crook, R. [ 14 ] showed that cement sheath failure will occur when there is a high internal casing pressure and is further aggravated by high-temperature conditions. Ding, L. et al [ 15 ] showed that casing failures can occur due to weak or failing cement plugs. These plugs can degrade due to several challenging conditions, such as acidic conditions, high salinity, high temperatures, and high pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Goodwin, K. and Crook, R. [ 14 ] showed that cement sheath failure will occur when there is a high internal casing pressure and is further aggravated by high-temperature conditions. Ding, L. et al [ 15 ] showed that casing failures can occur due to weak or failing cement plugs. These plugs can degrade due to several challenging conditions, such as acidic conditions, high salinity, high temperatures, and high pressure.…”
Section: Introductionmentioning
confidence: 99%